2012
DOI: 10.1186/1756-9966-31-80
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation status of Wnt antagonist SFRP5 can predict the response to the EGFR-tyrosine kinase inhibitor therapy in non-small cell lung cancer

Abstract: BackgroundIt is well known that genetic alternation of epidermal growth factor receptor (EGFR) plays critical roles in tumorgenesis of lung cancer and can predict outcome of non-small-cell lung cancer treatment, especially the EGFR tyrosine-kinase inhibitors (EGFR-TKIs) therapy. However, it is unclear whether epigenetic changes such as DNA methylation involve in the response to the EGFR-TKI therapy.MethodsTumor samples from 155 patients with stages IIIB to IV NSCLC who received EGFR-TKI therapy were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…2B and 2C). Multivariate analysis showed that Wif1 methylation exhibited a trend toward worse OS in AC patients with EGFR mutation (adjusted HR = 3.85, 95% CI = 0.79-18.72, P = 0.075) ( Table 2), being comparable with a recent observation that in ACs with EGFR mutation group, patients with methylated Wnt antagonist SFRP5 has a significantly shorter progression free survival than those with unmethylated SFRP5 (Zhu et al, 2012). Crosstalk between Wnt and EGFR signaling in cancers has been well documented (Hu et al, 2010).…”
supporting
confidence: 80%
“…2B and 2C). Multivariate analysis showed that Wif1 methylation exhibited a trend toward worse OS in AC patients with EGFR mutation (adjusted HR = 3.85, 95% CI = 0.79-18.72, P = 0.075) ( Table 2), being comparable with a recent observation that in ACs with EGFR mutation group, patients with methylated Wnt antagonist SFRP5 has a significantly shorter progression free survival than those with unmethylated SFRP5 (Zhu et al, 2012). Crosstalk between Wnt and EGFR signaling in cancers has been well documented (Hu et al, 2010).…”
supporting
confidence: 80%
“…Microarray-based screen pairing of the differential genetic profile of chemosensitive and chemoresistant cell lines have been reported (16)(17)(18)(19)(20) (21). However, only few reports focused on the relationship between egfr-tKi resistance and aberrant DNA methylation (22,23). Furthermore, DNA demethylating agent, 5-azacytidine, might increase the cellular sensitivity to gefitinib and control NSCLC cell growth and apoptosis (24).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of various components of Wnt pathway with shRNAs or small molecules significantly increased the efficacy of EGFR inhibitors both in vitro and in vivo (25). The DNA methylation status of the Wnt antagonist SFRP5 can predict the response to EGFR-TKI therapy in NSCLC (8). Wnt inhibitory factor 1 (Wif1) promoter methylation is an early and frequent event as an epigenetic field manner, and Wif1 hypermethylation can be as an unfavorable prognosis marker of NSCLC with EGFR mutation (26).…”
Section: Discussionmentioning
confidence: 99%
“…The pathway analysis of the differential methylated genes indicated that Wnt signaling pathway, Cadherin signaling pathway, and other pathways enriched in both patients are related to the EGFR pathway. Many studies have proven that Wnt signaling pathway has a role in EGFR-mutated lung cancer (8,25,26). Inhibition of various components of Wnt pathway with shRNAs or small molecules significantly increased the efficacy of EGFR inhibitors both in vitro and in vivo (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation